2018
DOI: 10.1001/jamaoto.2018.1663
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance in Thyroid Microcarcinoma in a Latin-American Cohort

Abstract: The incidence of thyroid carcinoma is growing worldwide owing to overdiagnosis. 1 Japanese authors have shown that active surveillance of patients with papillary thyroid microcarcinoma is possible. 2 Some case series have recently been published in Western countries, 3 but there are no reports from Latin America. The aim of this study is to report and describe a cohort of patients with thyroid nodules classified as Bethesda categories V to VI and who are under active surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 6 publications
2
25
0
1
Order By: Relevance
“…Regarding tumor progression, we recognize the short study period. Nevertheless, the initial results are similar to those reported in series with a longer follow-up time involving other populations [4][5][6][7]. A recent review of previous studies showed the absence of distant metastases in approximately 2500 patients with low-risk PTMC submitted to active surveillance, and only 1 % of the patients developed lymph node metastases apparent on US [3].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Regarding tumor progression, we recognize the short study period. Nevertheless, the initial results are similar to those reported in series with a longer follow-up time involving other populations [4][5][6][7]. A recent review of previous studies showed the absence of distant metastases in approximately 2500 patients with low-risk PTMC submitted to active surveillance, and only 1 % of the patients developed lymph node metastases apparent on US [3].…”
Section: Discussionsupporting
confidence: 79%
“…Since we had only one case of tumor progression, it was not possible to analyze predictive factors. As the most commonly found predictor, patient age has been related to the risk of tumor growth, which is higher in young individuals [4][5][6][7]. Interestingly, as observed in three of our patients, tumor reduction has also been reported in other series at a frequency ranging from 5-15 % [5, 6, 20, 21].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As a confirmation, several studies evaluating the lowrisk papillary thyroid microcarcinomas (mPTC) in adults (19)(20)(21)(22)(23) have shown that tumor growth is uncommon and that the development of apparent lymph node metastases is even rarer. So far there are no reports of the occurrence of distant metastases (Table 2).…”
Section: Papillary Thyroid Microcarcinomasmentioning
confidence: 94%